Philosophical Concept of Leadership in Supply Chain Affecting the Community Perception in the East Java Government of Indonesia - Robby Habiba Abror; Suraji Suraji; Moeheriono Moeheriono; Kholid Al Walid; Harjoni Harjoni (International Journal of Supply Chain Management, 2020)
This study aims to analyze the community perception towards the leadership style in supply chain that can be used to participate in the regional government. It also has a purpose to formulate a leadership style in supply chain that can encourage the community to actively participate in the local government. This study uses the descriptive qualitative approach to describe and explain the phenomenon of regional government leadership comprehensively. The research takes place in three regencies/ cities in East Java, Indonesia. The research finding shows that the public perception tends to choose the consultative, participative, and combination of both. The leadership style in supply chain is indicated by high involvement of public perception and trust given to subordinates. The leadership style in supply chain that is in line with the stakeholder’s expectation is the participative, consultative, and transformational styles.